Selection and use of English language software in Singapore primary schools - Lim, Kwee Keng. (2008)
It has been more than two years since the Masterplan for information technology (IT) in education was launched in April 1997. One major concern of many educationists is how well teachers have been coping with IT-based teaching. It is appropriate at this point of time to do a study to find out the problems teachers face in implementing the Masterplan and how the teaching and learning environment in Singapore is affected by the use of IT. The results drawn from the study will be useful for Ministry of Education (MOE) officials and teacher trainers as they will be able to tailor appropriate courses or workshops for teachers based on the findings.